“Not For An Age, But For All Time:” Autobiography and a Re-origin of Shakespeare Studies in Canada - Solá Chagas Lima, Eduardo; Thompson, Julie (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Despite independence as a country, Canada belongs to the Commonwealth and has deep colonial roots and the British educational system was key in creating Canadian curricula. Given the centrality of Shakespeare’s work in the British literary canon, it follows that it would also figure heavily in the academic requirements for Canadian students. At the dawn of the Confederation (1867), the high school curriculum used Shakespeare to emphasize a “humanist” approach to English literature using the traditional teaching methods of reading, rhetoric, and recitation. Presently, Shakespeare continues to be the only author in the high school curriculum to whom an independent area of study is dedicated. The origin of Shakespeare in Canada through curriculum and instruction is, thus, a result from the canonic tradition imported from Britain. This traditional model no longer fits the imperative of multiculturalism, as reflected in the Canadian Constitution Act (1982). Yet, with the appropriate methodology Shakespeare’s texts can be a vehicle for multiculturalism, social justice, and inclusivity. In light of recent disillusionments concerning the relevance of Shakespearean texts in high school curricula, this paper proposes an alternative pedagogical approach that envisages changing this paradigm and fostering a re-origin of Shakespeare studies in Canada through an intentional pedagogical process grounded in individual experience. Scholarship has highlighted the importance of autobiographies in the learning process and curriculum theorists William Pinar and Madeleine Grumet designed a framework that prioritizes individual experience. Our approach to teaching Shakespeare’s works aligns with the four steps of their currere method, presented as: (1) contemplative, (2) translational, (3) experiential, and (4) reconceptual, fostering an opportunity for self-transformation through trans-historical social themes present in the text. The central argument is that Shakespeare’s text can undergo a re-origin when lived, given its initial conception as embodied, enacted narrative in the early modern period. In this method, students immerse themselves in Shakespeare’s text through films and stage productions and then manifest their interpretations by embodying the literature based on their autobiographical narratives. To undergo a re-origin in the Canadian secondary curriculum, current pedagogical approaches to teaching Shakespeare require a paradigm shift.